Methodological aspects of the 1993 Pelotas (Brazil) birth cohort study Aspectos metodológicos da coorte de nascimentos de 1993 em Pelotas, RS - Cesar Gomes Victora; Cora Luiza Pavin Araújo; Ana Maria Batista Menezes; Pedro Curi Hallal; Maria de Fátima Vieira; Marilda Borges Neutzling; Helen Gonçalves; Neiva Cristina Valle; Rosangela Costa Lima; Luciana Anselmi; Dominique Behague; Denise Petrucci Gigante; et al. (Universidade de São Paulo, 2006)
This paper describes the main methodological aspects of a cohort study, with emphasis on its recent phases, which may be relevant to investigators planning to carry out similar studies. In 1993, a population based study was launched in Pelotas, Southern Brazil. All 5,249 newborns delivered in the city's hospitals were enrolled, and sub-samples were visited at the ages of one, three and six months and of one and four years. In 2004-5 it was possible to trace 87.5% of the cohort at the age of 10-12 years. Sub-studies are addressing issues related to oral health, psychological development and mental health, body composition, and ethnography. Birth cohort studies are essential for investigating the early determinants of adult disease and nutritional status, yet few such studies are available from low and middle-income countries where these determinants may differ from those documented in more developed settings. Descrever aspectos metodológicos do estudo da coorte de crianças que podem ser relevantes para pesquisadores que estejam planejando investigações semelhantes. Em 1993, uma coorte de base populacional foi recrutada em Pelotas, RS. Os 5.249 recém-nascidos nos hospitais da cidade foram acompanhados com um, três e seis meses, e com um e quatro anos de idade. Subestudos estão sendo realizados sobre saúde bucal, desenvolvimento psicológico e saúde mental, composição corporal e aspectos etnográficos. Em 2004-5 foi possível entrevistar 87,5% da coorte inicial, com a idade de 10-12 anos. Estudos de coortes de nascimentos são essenciais para investigar os determinantes precoces da morbidade e estado nutricional de adultos. No entanto, há poucos estudos com esta metodologia em países de renda média e baixa, e alguns dos determinantes da situação de saúde podem ser distintos daqueles observados em países ricos.